Comparitive Study Of Buckling And Bonding Behaviour Of Glass Fiber Reinforced Epoxy Resin Composite Column Under Compressive Loading Mechanism. - et. al., Srinath T, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Glass Fiber – reinforced polymer (GFPR) has been used as an alternative to steel due to high strength –to-weight ratio, high stiffness- to – weight ratio and corrosion and fatigue resistance. GFRP have been found to be more attractive in Asian region due to their cost competitiveness. Hence effort is required to find the bonding and buckling behaviors of fiber reinforced composite (FRC) column made using epoxy resin and glass fiber sheet with Triethylenetetramine (TETA) as hardener for curing of resin. To achieve the objective, an experimental setup was prepared with, specimen of hollow circular section is casted and compressive loading was applied to specimen. Numerical investigations have also been carried out using finite element analysis software ANSYS 13.0. load vs. Deflectioncurve, failure modes and ultimate load carrying capacity of specimens are presented in this work. This will help in finding the buckling nature of the section.